Inheritance of photoperiodic control of larval diapause in the Asian corn borer Ostrinia furnacalis (Guenée). Issue 3 (June 2015) - Xiao, L.; He, H.M.; Zhong, P.S.; Fu, S.; Chen, C.; Xue, F.S.
Abstract The Asian corn borer, Ostrinia furnacalis enters diapause as fully grown larvae. Owing to geographical variation in photoperiodic control of diapause, the subtropical strain from Hefei city (HF) enters diapause in response to short daylengths, whereas the tropical strain from Ledong county (LD) exhibits almost no diapause under the same conditions. The two strains were used in crosses to study the inheritance of diapause. The HF strain showed a typical long-day response with a critical daylength of approximately14.97 h at 22 °C, 14.60 h at 25 °C and 13.68 h at 28 °C. The LD strain showed weak photoperiodic responses at 22 and 25 °C; and the F1 progeny also showed a long-day response with significantly shorter critical daylength compared with the HF strain. However, the LD × HF (F × M) crosses had significantly longer critical daylengths than HF × LD crosses, indicating a sexual bias in the inheritance of diapause induction, with the male parent having more influence on the F1 progeny. The critical daylength in a backcross to HF was significantly longer than a backcross to LD. Whether the inheritance of diapause fits an additive hypothesis or not depended on photoperiod, with results from different photoperiods showing additive inheritance or incomplete dominance of either diapause or non-diapause. Unlike diapause induction, the duration of diapause for reciprocal crosses was equally influenced by each parent, suggesting that diapause incidence and maintenance are controlled by separate systems in O. furnacalis.